The Multimodal-Based Learning Improves Students' Reading Ability in Perspective of Systemic Functional Linguistics - Ridwin Purba; Herman Herman; Endang Fatmawati; Nanda Saputra; Yusniati N. Sabata (Universitas Pendidikan Ganesha, 2023)
This study was encouraged by taking advantage of the low analytical literacy abilities of students in junior high schools. This research aims to analyze Multimodal-Based Learning in Improving Students' Reading Ability from a Systemic Functional Linguistic Perspective. This research was conducted using quantitative research, incredibly descriptive, and experimental research. Data is collected through comment sheets and ratings. The respondents in this study were 210 students and nine teachers in seven classes. The tools used to obtain learning statistics are (1) an assessment to measure the competence of junior high school students and (2) note sheets to obtain statistics on the results of looking at the learning system. The statistics have been processed using descriptive statistical judgments and inferential facts. Based on the research results, the analytical learning system in the classroom still does not meet the actual learning requirements. The second result is that the multimodality method has proven effective in analyzing the literacy talents of junior high school students from various backgrounds. Based on this, the multimodality learning method can be used to improve the analytical literacy talents of junior high school students in classes with various backgrounds.